Reimplementation of madrasah ramah anak in building discipline character of students - Awaluddin, Raisa Zuhra Salsabila; Sabililhaq, Irhas; Nida, Sofwatun (UIN Salatiga, 2024)
This study aims to discuss the implementation and impact of the Madrasah Ramah Anak (MRA) concept on the disciplinary character of students. This study uses a qualitative approach of field research type. This research took place at MAN 1 Sleman. Data collection was conducted through interviews and purposive sampling techniques. The results showed that the MRA program has been implemented following Sekolah Ramah Anak's (SRA) component. They are child-friendly school policy, educators and education personnel trained in children's rights and SRA, child-friendly learning process, child-friendly facilities and infrastructure, and child participation. MRA provides significant changes by shifting rewards and punishments towards a more humanist approach. The implementation of MRA, which is based on Albert Bandura's modeling theory, allows students to imitate the behavior of educators and peers. This modeling involves all madrasah stakeholders. The positive impact is the application of the principle of justice and increased networking with external parties such as BKKBN and Puskesmas. Then, the negative impact is the weakening of students' disciplinary attitude because they seem to feel safe from punishment. The solutions include involving students in competitions and formulating rules-related class agreements. This research is expected to make a scientific contribution to the formation of disciplinary character, especially through the concept of MRA.